From the Murray to the Mekong: Grant Evans' life and fieldwork - Cox, Peter (The Australian journal of anthropology, 2019)
This article presents glimpses of the life and fieldwork of Grant Evans, the foremost anthropologist and historian to work on Laos in recent decades. It explores his youth in rural Australia, his tumultuous student years, and the challenges he faced as a professional scholar negotiating the Lao PDR bureaucracy. It draws insights from some of his early writing for alternative publications in Australia, as well as extensive discussions and correspondence with family, friends, professional counterparts and former students. It identifies factors in Grant's early life that were instrumental in his ability to research the Lao PDR. Ultimately, Grant possessed wide-ranging academic and non-academic interests. He was highly respected as a scholar and was a very decent human being.